Home making, one of the highest professions - Harman, Mary Frances Burgoyne (My University, 1893)
Introduction: The home has been the basis of all the genuine, all the lasting improvement in the race. Hence, judging the future by the past, it is to the home that we turn for the most effective work in the solution of the great problems of the time.
Citation: Harman, Mary Frances Burgoyne. Home making, one of the highest professions. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Home; Race; Solution; Theses; Manuscripts (documents)